Impaired Autophagy of GABAergic Interneurons in Neuropathic Pain - Yuhua Yin; Min-Hee Yi; Dong Woon Kim (Pain Research and Management)
Neuropathic pain (NP) is caused by lesions of the peripheral fibers and central neurons in the somatosensory nervous system and affects 7–10% of the general population. Although the distinct cause of neuropathic pain has been investigated in primary afferent neurons over the years, pain modulation by central sensitization remains controversial. NP is believed to be driven by cell type-specific spinal synaptic plasticity in the dorsal horn. Upon intense afferent stimulation, spinothalamic tract neurons are potentiated, whereas GABAergic interneurons are inhibited leading to long-term depression. Growing evidences suggest that the inhibition of GABAergic neurons plays pivotal roles in the manifestation of neuropathic and inflammatory pain states. Downregulation of GABA transmission and impairment of GABAergic interneurons in the dorsal horn are critical consequences after spinal cord and peripheral nerve injuries. These impairments in GABAergic interneurons may be associated with dysfunctional autophagy, resulting in neuropathic pain. Here, we review an emerging number of investigations that suggest a pivotal role of impaired autophagy of GABAergic interneurons in NP. We discuss relevant research spurring the development of new targets and therapeutic agents of NP and emphasize the need for a multidisciplinary approach to manage NP in the future.